Studi Fenomenologi Gambaran Kehidupan Religiusitas bagi Lanjut Usia di Masa Pandemi - Lilyana, Maria Theresia Arie; Cempaka, Anindya Arum (JURNAL KESEHATAN PRIMER, 2022)
Introduction: religiosity is one of the supporters of a healthy life and a long life for the elderly. The pandemic has impacted the elderly, especially the implementation of the Enforcement of Restrictions on Community Activities, especially in religious life as a basic form of religiosity. The purpose of this study was to determine the religious experience of the elderly during the Covid-19 pandemic. Methods: qualitative, with 10 participants who met the inclusion criteria, participated in this study. The researcher conducted a thematic analysis by repeatedly reading the results of the verbatim transcript to look for patterns of meaning to find themes. Results: in the form of research themes, namely: the form of religiosity that is interpreted as elderly, the benefits of religiosity for the life of the elderly, solutions to meet the needs of religiosity during the pandemic, and the expectations of the elderly in fulfilling the needs of religiosity. Religiosity is carried out both in prayer life and in applying religious teachings in the form of kindness to others. Religiosity provides a sense of calm and comfort and guides the life of the elderly. Older people practice religiosity during a pandemic by praying privately and participating in online prayer activities. Conclusion: It is essential to pay attention to religious life to be able to provide meaning and benefit to the life of the elderly. The elderly feel satisfied with their life because of the support of the people around them and, finally, experience long life and a good quality of life.